USING PLANT TISSUE CULTURE TECHNIQUE TO EVALUATE FOUR GENOTYPES OF MAIZE TO SALINITY TOLERANCE - Salih , M.; Abed , A.; Ismail , E.; Kassad , S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Salinity is an important abiotic factor that negatively impacts maize cultivation, especially in areas with saline soils. The present study evaluates the influence of salinity on the growth and physiological reactions of seven maize genotypes. Highly tolerant cultivars were excluded, while callus cultures were produced from moderately salt-tolerant cultivars and salt-sensitive genotypes on MS medium fortified with 3 mg/L 2,4-D and 0.5 mg/L Kin. The finding showed that high levels of salinity significantly decreased the callus weight. The moderate cultivars (Alfajr and Almaha) demonstrated a high salt tolerance index (STI) compared with sensitive genotypes (T1 and T6).  The ionic analysis indicated that genotypes T1 and T6 revealed a higher concentration of the ions Na+ and Cl-. On the contrary, the cultivars Alfajr and Almaha accumulated a high concentration of the cations K+ and Ca2+, along with a greater carbohydrates and proline content, that probably led to their developed salt tolerance. Additionally, the molecular analysis based on the RAPD test, classified the tolerant cultivars and sensitive genotypes into two separate groups, confirming the presence of genetic differences related to salinity tolerance. The results highlight the role of ion regulation, osmotic adaptation, and genetic factors to mitigate the impact of salinity on maize. The study provides helpful insights that could assist breeding procedures for developing salt-tolerant maize genotypes that are necessary for maintaining maize agriculture in areas affected by high salt stress.